The strength of cement - Savage, James G.; Edgerton, Glen Edgar (My University, 1904)
Introduction: A knowledge of the values of different brands of cement is becoming more and more desirable as cement and concrete are becoming more and more extensively used in modern engineering constructions. So many different brands of cement are now upon the market that considerable difficulty may be met with in selecting a cement to fill any given specifications. The following tests were made upon four of the more common cements found in the hands of dealers and contractors at Manhattan, Kansas. The cement tested were two naturals and two Portlands: (1). Louisville Natural Cement, made in cement works on the Ohio river. By Manhattan dealers it is obtained from wholesale agencies in Kansas City. The cement is of a light brown color with a slight tendency toward purple, the briquette after setting a short time exhibiting a distinct tinge of purple. Its apparent density is about seventy-seven hundredths. (2). Fort Scott Cement, a natural cement made by the Fort Scott Cement Association at Fort Scott, Kansas. Its color is light brown bordering on yellow, somewhat darker than straw color. Its apparent density is about eighty hundredths…
Tests on the tensile and compressive strength of cement
Citation: Savage, James G. and Edgerton, Glen Edgar. The strength of cement. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Cement; Material Science; Construction Materials; Theses